Reliability analysis for blockchain oracles. (May 2020) - Lo, Sin Kuang; Xu, Xiwei; Staples, Mark; Yao, Lina
Abstract: Blockchain is an emerging technology that is increasingly supporting economic-ally-critical systems. The execution environment of blockchain is isolated from the external world and thus requires "blockchain oracles": agents that fetch information from the external world. Blockchain is known to be highly reliable, but oracles are off-chain components that could be points of failure in whole blockchain-based systems. The reliability of blockchain oracles has yet to be investigated. In this paper, we propose a framework to compare and characterize existing blockchain oracles mechanisms from industry. Our approach for reliability modelling and architecture analysis of blockchain oracle systems uses Fault Tree Analysis. By calculating the reliability of oracles mechanisms, we can identify weak links that affect the overall reliability of a blockchain-based system.